Գանձասարի կաթողիկոս Գրիգոր Հասան-Ջալալյանի ուրացության հարցի շուրջ (XVI դար) - Մաղալյան, Արտակ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
В Гавазанагирке (хронологическом списке католикосов) Алуанка (Гандзасара) и в различных хрониках упоминается о католикосе Григоре АсанДжалаляне, отрекшемся от христианства в XVI веке. Долгое время эта инфор- мация оставалась загадкой. Однако после публикации (в 1970 г.) памятной записи Евангелия пера иеромонаха Абраама, хранившегося под номером 33 в библиотеке монастыря Аменапркич Нор Джуги, выяснилось, что католикос Григор в 1574 г. был насильственно обращен в ислам сефевидским шахом Тахмаспом I (1524–1576). In the Gavazanagirq (chronological list of Catholicoi) from Alwanq (Gandzasar) and in various chronicles, there are references to Catholicos Grigor Hasan-Jalalyan, who renounced Christianity in the 16th century. For a long time, this information remained a mystery. However, after the publication (in 1970) of the memorial records of the Gospel written by hieromonk Abraham, kept under number 33 in the library of the Amenaprkich Monastery of Nor Jugha, it became known that Catholicos Grigor was forcibly converted to Islam in 1574 by Safavid Shah Tahmasp I (1524–1576).
Keywords: Պատմություն; Եկեղեցու գործիչներ